Retrieval of the Leadless Cardiac Pacemaker: A Multicenter Experience. (December 2016) - Reddy, Vivek Y.; Miller, Marc A.; Knops, Reinoud E.; Neuzil, Petr; Defaye, Pascal; Jung, Werner; Doshi, Rahul; Castellani, Mark; Strickberger, Adam; Mead, R. Hardwin; Doppalapudi, Harish; Lakkireddy, Dhanunjaya; et al.
Abstract : Background—: Leadless cardiac pacemakers have emerged as a safe and effective alternative to conventional transvenous single-chamber ventricular pacemakers. Herein, we report a multicenter experience on the feasibility and safety of acute retrieval (<6 weeks) and chronic retrieval (>6 weeks) of the leadless cardiac pacemaker in humans. Methods and Results—: This study included patients enrolled in 3 multicenter trials, who received a leadless cardiac pacemaker implant and who subsequently underwent a device removal attempt. The overall leadless pacemaker retrieval success rate was 94%: for patients whose leadless cardiac pacemaker had been implanted for <6 weeks (acute retrieval cohort), complete retrieval was achieved in 100% (n=5/5); for those implanted for ≥ 6 weeks (chronic retrieval cohort), retrieval was achieved in 91% (n=10/11) of patients. The mean duration of time from implant to retrieval attempt was 346 days (range, 88–1188 days) in the chronic retrieval cohort, and nearly two thirds (n=7; 63%) had been implanted for >6 months before the retrieval attempt. There were no procedure-related adverse events at 30 days post retrieval procedure. Conclusions—: This multicenter experience demonstrated the feasibility and safety of retrieving a chronically implanted single-chamber (right ventricle) active fixation leadless pacemaker. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifiers: NCT02051972, NCT02030418, and NCT01700244.